Mental Health in Women With Traumatic Brain Injury: A Systematic Review on Depression and Hope. Issue 1 (2nd January 2016) - Oyesanya, Tolu O.; Ward, Earlise C.
Abstract : The prevalence of traumatic brain injury (TBI) in women has recently increased from 25% to 40%. Current literature inadequately captures challenges women face after injury, including depression. The limited focus on depression is problematic as rates of depression are increasing simultaneously with rates of TBI. A disabling symptom of depression is lack of hope; thus, depression, comorbid with TBI, leads to disability among women. Unfortunately, depression and hope among women with TBI has yet to be systematically examined. The purpose of this systematic review is to examine and synthesize current literature focusing on women with TBI, comorbid with depression, and hope.